Pengaruh Struktur Modal, Pertumbuhan Perusahaan dan Keputusan Investasi terhadap Nilai Perusahaan - Dilena, Rohati; Oktavianna, Rakhmawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of capital structure, firm growth, and investment decisions on firm value. This study uses the dependent variable of firm value and the independent variables of capital structure, company growth, and investment decisions. The population in this study are non-cyclicals consumer sector companies listed on the Indonesia Stock Exchange period 2018-2022. The total population or companies in the non-cyclicals consumer sector is 113 companies. From this population, purposive sampling technique is used with several criteria to determine a sample of 16 companies. The data analysis technique in this study uses Eviews 12 which includes descriptive statistical tests, panel data model analysis, classical assumption tests and hypothesis testing. Based on the test results above, it proves that capital structure, company growth, and investment decisions simultaneously affect firm value. Partially, capital structure has no effect on firm value, company growth affects firm value, and investment decisions affect firm value.